Research on the Evolution Characteristics of Rock Mass Response from Open-Pit to Underground Mining. (9th August 2021) - Geng, Jiabo; Li, Qihang; Li, Xiaoshuang; Zhou, Tao; Liu, Zhifang; Xie, Yulin
Abstract : This study is based on the engineering background of pit no. 2 in Jinning Phosphate Mine, China. In order to systematically analyze the movement, deformation, and failure laws of surrounding rocks in underground stopes. The room and pillar method is used to excavate and stop the ore bodies in the mining area. Combined with the similar physical model experiments and discrete element MatDEM numerical simulations, it reveals the deformation and failure laws and evolution characteristics of the surrounding rock of the stope in the process of converting from open-pit to underground mining. The results show the following: (1) Along the inclination of the ore body, the farther the horizontal and vertical displacements are from the underground stope, the less the impact of mining stress. On the other hand, along the inclined vertical direction of the ore body, the farther the measuring point is from the stope, the smaller the range of mining influence will be. (2) In the process of ore body recovery, the rupture of the overlying strata of the stope has an obvious layered structure, with collapse zones, fissure penetrating zones, and microfracture loosen zones appearing from the bottom to top. In addition, the movement and destruction of the overlying strata of the entire stope is an "elliptical arch." Therefore, the results of similar simulation experiments and numerical simulation are basically consistent.